Large-size composite setter board and preparation method thereof

By setting up the main layer and interface layer of the zircon in the large-scale composite burning plate, the zircon corundum mullite complex phase network interleaving structure is formed, which solves the problem of thermal shock cracking of the burning plate under high temperature conditions, and significantly improves the service life and performance.

CN119504241AActive Publication Date: 2025-02-25JIANGSU SANHENG HIGH-TECH KILN FURNITURE CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411665732.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-25
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

Large-size composite burning plates are prone to thermal shock cracking, internal and external cracks or cracks under high temperature conditions, resulting in a short service life, usually only about 50 times.

Method used

The stacked firing method is adopted, and the bonding layer is arranged, which consists of zircon as the main layer and the interface layer. The interface layer uses activated silica and alumina micropowder to form a zirconium corundum mullite complex phase interleaving structure containing benign zirconium crystal phase doping toughened, enhancing the bonding strength and thermal shock resistance.

Benefits of technology

It significantly improves the bonding strength and thermal shock resistance of large-size composite burning plates, extends the service life to more than 80 times, reduces manufacturing costs, and improves economics and competitiveness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005144529800000071
    Figure BDA0005144529800000071
  • Figure BDA0005144529800000081
    Figure BDA0005144529800000081
  • Figure BDA0005144529800000091
    Figure BDA0005144529800000091
Patent Text Reader

Abstract

The invention belongs to the field of advanced structure ceramic preparation, and particularly relates to a large-size composite setter plate and a preparation method thereof. An outer surface layer of the load bearing plate is a load bearing isolation layer with tabular corundum as a main body, an inner surface layer of the load bearing plate is a load bearing supporting layer with silicon carbide as a main body, a bonding layer is arranged between the outer surface layer and the inner surface layer, and the bonding layer is composed of zirconite as a main body layer, an upper interface layer and a lower interface layer. The preparation method comprises the following steps: mixing the raw materials, scraping the materials, uniformly distributing the materials, performing high-pressure forming, drying a green body, and sintering at 1400-1550 DEG C to obtain the composite load bearing plate with excellent thermal shock resistance and good bonding strength. According to the invention, through innovation and process setting of the bonding layer, the problems of thermal shock cracking and inner and outer layer peeling of the setter plate caused by large-size factors are solved, the service life of the composite setter plate is prolonged to more than 80 times, and the economical efficiency and competitiveness of the setter plate in use are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of advanced structural ceramic preparation, and in particular relates to a large-size composite setter plate and a preparation method thereof. Background Art

[0002] Composite setter is a kiln tool for sintering electronic components. It is generally a composite structure with silicon carbide as the middle layer and alumina as the wrapping layer. The middle layer uses the high-temperature flexural strength and good thermal shock resistance of silicon carbide to provide good bearing strength and thermal shock resistance for the setter. The outer layer of alumina of the composite setter can play an isolating role. For example, electronic components represented by magnetic materials contain elements such as iron, oxygen, manganese, and zinc, which are easy to react with elements such as silicon during high-temperature sintering. The outer alumina layer of the composite setter directly contacts the setter product, which can reduce the volatilization of impurities in the inner layer material and cause contamination of the magnetic material. At present, large-sized composite setters are more prone to thermal shock cracking under high-temperature load conditions. After repeated use, cracks or cracks are prone to occur between the inner and outer layers, and even delamination or peeling occurs, which seriously affects the service life of the composite setter.

[0003] Chinese Patent: CN202322165986.5 discloses a large-sized composite support plate with a breathable bearing surface. By setting a boss on the loading surface of the support plate, the fluidity of the firing atmosphere on the bearing surface of the large-sized support plate for electronic components is greatly improved, making the firing atmosphere around the entire electronic component more uniform and more breathable. At the same time, it avoids the situation where the surface of the support plate is perforated and the high-temperature atmosphere of the inner layer of silicon carbide is volatilized to pollute the components and affect the performance of the electronic components; it can meet the sintering requirements of electronic components and the technical characteristics requirements of high-performance electronic components, and the effect is remarkable. The large-sized composite support plate has enhanced the fluidity of the atmosphere and avoided the pollution of the openings through structural improvements. However, under actual high-temperature use conditions, due to the large size and specifications, the original raw material ratio and structural settings are used, the joints of the composite support plate are prone to cracking or falling off, and the entire board surface is also prone to thermal shock cracking, which affects the service life of the composite support plate. The general number of uses is only about 50 times. Summary of the invention

[0004] In view of the above shortcomings, the present invention provides a large-size composite setter plate, which has good bonding strength and thermal shock resistance and a long service life.

[0005] According to a specific embodiment of the present invention, a large-scale composite setter is fired by a stacked body, and the stacked body comprises, in parts by weight from top to bottom: 5 to 10 parts of a plate-like corundum outer layer, 6 to 10 parts of a bonding layer, 60 to 70 parts of a silicon carbide inner layer, 6 to 10 parts of a bonding layer, and 5 to 10 parts of a plate-like corundum outer layer, wherein:

[0006] The bonding layer includes an interface material layer, a main material layer, and an interface material layer from top to bottom, and the mass ratio of the interface material layer, the main material layer, and the interface material layer is 1-2:8-9:1-2;

[0007] In parts by weight, the raw materials for preparing the interface material layer include:

[0008] Active silicon dioxide ≤50um 0.5~1.0 parts,

[0009] Alumina powder ≤50um 1-2 parts,

[0010] In terms of weight, the raw materials for preparing the main material layer include:

[0011] Zircon 0.075~0.15mm 8~9 parts.

[0012] The outer layer of the support plate of the present invention is mainly composed of plate-shaped corundum, and the inner layer is a load-bearing support layer mainly composed of silicon carbide. A bonding layer is arranged between the outer layer and the inner layer, and the bonding layer is composed of zircon as a main layer and upper and lower interface layers.

[0013] According to the large-scale composite setter plate of the specific embodiment of the present invention, the raw materials for preparing the outer layer of the plate-like corundum include, by weight:

[0014] Plate-shaped corundum powder ≤50um 5.0~6.0 parts,

[0015] Plate-shaped corundum 0.075~0.18mm 3.0~4.0 parts,

[0016] Alumina powder ≤50um 0.5~1.0 part.

[0017] According to a specific embodiment of the present invention, the large-scale composite setter plate, in parts by weight, the raw materials for preparing the silicon carbide inner layer include:

[0018] Silicon carbide 0.6~2mm 3.5~5.0 parts,

[0019] Silicon carbide 0.125~0.25mm 3.0~4.5 parts,

[0020] Silicon carbide ≤50um 1.0~2.0 parts,

[0021] Kaolin 0.045~0.075mm 1.0~2.0 parts.

[0022] According to a specific embodiment of the present invention, a method for preparing a large-sized composite setter plate comprises the following steps:

[0023] (1) Stacking molding: placing the raw materials into a mold in sequence to obtain a stacked body, wherein the stacked body comprises, from top to bottom, a plate-shaped corundum outer layer, a bonding layer, a silicon carbide inner layer, a bonding layer, and a plate-shaped corundum outer layer; after high-pressure molding, a molded blank is obtained;

[0024] The bonding layer is composed of interface material layer, main material layer and interface material layer from top to bottom.

[0025] In parts by weight, the raw materials for preparing the interface material layer include:

[0026] Active silicon dioxide ≤50um 0.5~1.0 parts,

[0027] Alumina powder ≤50um 1-2 parts,

[0028] In terms of weight, the raw materials for preparing the main material layer include:

[0029] Zircon 0.075~0.15mm 8~9 parts.

[0030] (2) drying the formed blank until the moisture content is less than 1.5% to obtain a dry blank;

[0031] (3) Sintering the dry blank at 1400-1550°C and keeping it warm for 3-5 hours to obtain a combined fired plate.

[0032] Preferably, the formed blank is naturally stored for 24 to 48 hours, and after the internal stress is released, it is placed in a drying room for drying, and after drying at a temperature of 60 to 100° C., a dry blank with a moisture content of less than 1.5% is obtained, which is ready for loading into the kiln.

[0033] Preferably, the raw material of the main material layer is prepared by taking 8.0-9.0 parts of zircon with a size of 0.075-0.15 mm, adding PVA aqueous solution, and mixing evenly to obtain a main material layer liquid with a water content of 3-6%.

[0034] Preferably, the raw material preparation method of the interface material layer is as follows: 0.5-1.0 parts of active silicon dioxide ≤50um and 1.0-2.0 parts of alumina powder ≤50um are added to a PVA aqueous solution, and mixed evenly to obtain an interface material solution having a water content of 2-5%.

[0035] Preferably, the thickness of the main material layer is 1 to 1.5 mm, and the thickness of the interface material layer is 0.1 to 0.5 mm. During the firing process, the interface layer interpenetrates with the inner layer and the outer layer. The main material layer of the bonding layer partially dissociates into a silica liquid phase and a monoclinic zirconium dioxide phase under high temperature conditions, and reacts with the active silica and alumina powder mixture of the interface layer to form a zirconium corundum mullite complex network interlaced structure doped with a badly zirconium crystal phase and toughened.

[0036] The active silica and alumina powder mixture of the interface layer and the plate-shaped corundum and alumina powder of the outer layer are pressed by high-pressure molding, and the bonding force between the particles is enhanced. Under high temperature conditions, a corundum-mullite complex structure is generated to enhance the bonding strength between the bonding layer and the outer layer, and has good bonding strength and excellent thermal shock resistance.

[0037] The interfacial active silica and alumina powder mixture reacts with the silica in kaolin in the inner layer material and the silica produced by high-temperature oxidation of silicon carbide to form a corundum-mullite complex phase structure under high temperature conditions, which enhances the bonding strength between the bonding layer and the inner layer, and has good bonding strength and excellent thermal shock resistance.

[0038] Preferably, the method for preparing the raw materials for the outer layer of plate-like corundum is as follows: 5.0-6.0 parts of plate-like corundum powder ≤50um, 3.0-4.0 parts of plate-like corundum 0.075-0.18mm, and 0.5-1.0 parts of alumina powder ≤50um are added, a PVA aqueous solution is added, and mixed evenly to obtain an outer layer liquid having a water content of 3-6%.

[0039] Preferably, the method for preparing the raw materials for the silicon carbide inner layer is as follows: take 3.5-5.0 parts of silicon carbide 0.6-2mm, 3.0-4.5 parts of silicon carbide 0.125-0.25mm, 1.0-2.0 parts of silicon carbide ≤50um, and 1.0-2.0 parts of kaolin 0.045-0.075mm, add PVA and mix evenly to obtain an inner layer liquid having a water content of 3-8%.

[0040] Beneficial effects of the present invention:

[0041] The present invention, based on a full understanding of the main reasons for damage caused by the use of large-sized composite support plates, greatly enhances the bonding strength and thermal shock resistance of the support plates through innovation of the bonding layer and improvement of the process, solves the problems of thermal shock cracking and peeling of the inner and outer layers of the support plates caused by large size factors, and increases the service life of the composite support plates to more than 80 times, thereby reducing the manufacturing cost of the user unit and improving the economy and competitiveness of the use of the support plates.

[0042] The bonding layer material uses zircon as the main raw material, and the interface material is a mixture of active silica powder and alumina powder. Among them, zircon has a small thermal expansion coefficient and good toughness. Zircon fine powder of 0.075-0.15 mm is selected and sintered under high temperature conditions. Most of it is decomposed into a baddeleyite crystal phase and a silica liquid phase, which can react with the active silica powder and alumina powder of the interface material to form a columnar mullite network complex phase interlaced structure doped with a baddeleyite crystal phase and toughened, which has good bonding strength and excellent thermal shock resistance.

[0043] The present invention optimizes the particle gradation of silicon carbide in the inner layer material and adopts a stacked material distribution method, so that the active silicon dioxide micropowder and alumina micropowder in the interface material can be partially embedded in the gaps between silicon carbide particles. After the firing reaction, the silicon dioxide in the kaolin of the inner layer material and the silicon dioxide generated by the high-temperature oxidation of silicon carbide form an integrated mullite network complex interlaced structure with the bonding layer, and can also improve the bearing performance and thermal shock resistance of the silicon carbide base layer of the setter plate.

[0044] The optimized particle size distribution and composition of the outer layer material, after the sintering reaction, the plate-shaped corundum powder is more conducive to the formation of a mullite network complex interlaced structure together with the active silica powder and alumina powder of the interface layer, thereby improving the bonding strength and anti-stripping performance of the support plate. DETAILED DESCRIPTION

[0045] To make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.

[0046] In the present invention, the large-size setter refers to a setter with at least one side having a length of ≥350 mm.

[0047] The present invention provides a method for preparing a large-size composite setter plate, comprising the following steps:

[0048] (1) Raw material preparation:

[0049] Outer material:

[0050] Mix 5.0-6.0 parts by mass of plate-shaped corundum powder ≤50um, 3.0-4.0 parts by mass of plate-shaped corundum 0.075-0.18mm, and 0.5-1.0 parts by mass of alumina powder ≤50um, add PVA aqueous solution to obtain an outer layer liquid, the water content of the outer layer liquid is 3-6%, and the material is set aside for use.

[0051] Main material: 8.0-9.0 parts of zircon 0.075-0.15 mm, put into a three-dimensional mixer, add PVA aqueous solution, mix evenly to obtain the main material liquid, the water content of which is 3-6%, and the material is set aside;

[0052] Interface layer material: 0.5-1.0 part of active silicon dioxide ≤50um, 1.0-2.0 part of alumina powder ≤50um, add PVA aqueous solution, mix evenly, and obtain interface layer liquid, the moisture content of which is 2-5%, and store the material for later use. The active silicon dioxide powder and alumina powder are both powders treated by spray granulation;

[0053] Inner layer material: add PVA aqueous solution to 3.5-5.0 parts by mass of silicon carbide 0.6-2mm, 3.0-4.5 parts by mass of silicon carbide 0.125-0.25mm, 1.0-2.0 parts by mass of silicon carbide ≤50um, and 1.0-2.0 parts by mass of kaolin 0.045-0.075mm, and mix well to obtain inner layer liquid with a water content of 3-8%. The material is set aside for later use.

[0054] (2) Stacking molding:

[0055] The outer layer material, bonding layer material, interface layer material and inner layer mixed material which have been trapped for 24 to 36 hours are layered into the mold in the order of outer layer material, bonding layer material, interface layer material, bonding layer material, inner layer material, bonding layer material, interface layer material, bonding layer material and outer layer material to obtain a stacked body. In terms of weight parts, the stacked body comprises from top to bottom: 5 to 10 parts of a plate-like corundum outer layer, 6 to 10 parts of a bonding layer, 60 to 70 parts of a silicon carbide inner layer, 6 to 10 parts of a bonding layer and 5 to 10 parts of a plate-like corundum outer layer, wherein:

[0056] In terms of weight, the bonding layer includes, from top to bottom, 1.0 to 2.0 parts of the interface material layer, 8.0 to 9.0 parts of the main material layer, and 1.0 to 2.0 parts of the interface material layer;

[0057] The stacked body is subjected to high pressure forming to obtain a formed blank;

[0058] (3) drying the formed blank until the moisture content is less than 1.5% to obtain a dry blank;

[0059] (4) High temperature firing:

[0060] The dried qualified blanks are sintered at 1400-1550°C and kept warm for 3-5 hours to obtain large-sized composite support plates with good bonding strength and excellent thermal shock resistance.

[0061] Preferably, the weight proportion of plate-shaped corundum powder ≤50 um is 5.2 to 5.7 parts, the weight proportion of plate-shaped corundum 0.075 to 0.18 mm is 3.2 to 3.8 parts, and the weight proportion of alumina powder ≤50 um is 0.6 to 0.8 parts.

[0062] Preferably, the plate-like corundum micropowder and alumina micropowder are powders that have been subjected to a spray granulation process.

[0063] Preferably, zircon is 0.075-0.15 mm and 8.2-8.8 parts, and the water content of the inner layer liquid is preferably 4-5%.

[0064] Preferably, the active silicon dioxide ≤50 um is 0.6-0.8 parts, the alumina powder ≤50 um 1.0- is 1.3-1.8 parts, and the water content of the interface layer liquid is preferably 3-4%.

[0065] Preferably, the active silicon dioxide micropowder and the aluminum oxide micropowder are both powders that have been subjected to spray granulation treatment.

[0066] Preferably, silicon carbide 0.6-2mm is 3.8-4.6 parts, silicon carbide 0.125-0.25mm is 3.4-4.2 parts, silicon carbide ≤50um is 1.4-1.8 parts, kaolin 0.045-0.075mm is 1.2-1.8 parts, and the water content of the inner layer liquid is preferably 3-4%.

[0067] The mass concentration of the PVA aqueous solution is preferably 1-1.5%.

[0068] Preferably, the stacked body is subjected to high-pressure molding by applying a pressure of 150-200 MPa through a molding hydraulic press to obtain a molded blank; the molded blank is naturally stored for 24-48 hours, and after the internal stress is released, it is placed in a drying room for drying, and after drying at a temperature of 60-100°C, a dry blank with a moisture content of less than 1.5% is obtained, which is ready for loading into the kiln.

[0069] Preferably, the high temperature sintering system of the present invention is:

[0070]

[0071] Example 1

[0072] The method for preparing the large-size composite setter plate of the present invention comprises the following steps:

[0073] 1. Preparation of raw materials:

[0074] Outer layer material: put 5.0 parts of plate-shaped corundum powder ≤50um, 3.0 parts of plate-shaped corundum 0.075~0.18mm, and 0.5 parts of alumina powder ≤50um into a three-dimensional mixer, dry mix for 0.5 hours, add 1% PVA aqueous solution, and mix for another 0.5~1 hour, mix evenly, and control the moisture content of the outer layer liquid to 3%. The materials are set aside for use, wherein the plate-shaped corundum powder and alumina powder are powders that have been treated by spray granulation;

[0075] Main material: 8.0 parts of zircon 0.075-0.15mm, put into a three-dimensional mixer, add 1% PVA aqueous solution, mix for 0.5 hours, mix evenly, control the water content of the main material liquid to 3%, and set aside;

[0076] Interface layer material: 0.5 part of active silica ≤50um, 1.0 part of alumina powder ≤50um, put into a three-dimensional mixer, add 1% PVA aqueous solution, mix for 0.5 hours, mix evenly, control the moisture content of the interface layer liquid at 2%, and set aside, wherein the active silica powder and alumina powder are powders that have been spray granulated;

[0077] Inner layer material: put 3.5 parts of silicon carbide 0.6-2mm, 3.0 parts of silicon carbide 0.125-0.25mm, 1.0 part of silicon carbide ≤50um, and 1.0 part of kaolin 0.045-0.075mm into a mixer, dry mix for 0.5 hour, add 1% PVA aqueous solution, and mix for another 0.5 hour. Mix evenly, and control the moisture content of the inner layer material to 3%. Set aside the material for later use;

[0078] 2. Pressing and drying of molding:

[0079] Take 1 / 2 outer layer material, 1 / 4 interface layer material, 1 / 2 bonding layer material, 1 / 4 interface material, inner layer material, 1 / 4 interface material, 1 / 2 bonding layer material, 1 / 4 interface material, 1 / 2 outer layer material, and place them in sequence into the mold cavity. After scraping and leveling the material, apply 100MPa pressure through a molding hydraulic press for high pressure molding to obtain a molded blank;

[0080] In terms of weight, there are 5 parts of plate-like corundum outer layer, 6 parts of bonding layer, 60 parts of silicon carbide inner layer, 6 parts of bonding layer and 5 parts of plate-like corundum outer layer; the mass ratio of interface material layer, main material layer and interface material layer is 1:8:1.

[0081] The formed blanks are naturally stored for 24 hours, and after releasing the internal stress, they are placed in a drying room for drying. After drying at 60°C, dry blanks with a moisture content of less than 1.5% are obtained, which are ready for loading into the kiln.

[0082] 3. High temperature firing:

[0083] The dried qualified blanks are sintered through the following procedures to obtain large-sized composite setter plates.

[0084]

[0085]

[0086] Example 2

[0087] The method for preparing the large-size composite setter plate of the present invention comprises the following steps:

[0088] 1. Preparation of raw materials:

[0089] Outer layer material: put 5.5 parts of plate-shaped corundum powder ≤50um, 3.5 parts of plate-shaped corundum 0.075~0.18mm, and 0.8 parts of alumina powder ≤50um into a three-dimensional mixer, dry mix for 0.8 hours, add 1.2% PVA aqueous solution, and mix for another 0.8 hours to obtain a uniform mixture. The moisture content of the mixture is controlled at 4%, and the mixture is set aside for use. The plate-shaped corundum powder and alumina powder are powders that have been spray granulated;

[0090] Main material: 8.5 parts of zircon with a size of 0.075-0.15 mm, put into a three-dimensional mixer, add 1.2% PVA aqueous solution, mix for 0.8 hours, and obtain the main material liquid with a water content of 4%. The material is stored for later use;

[0091] Interface layer material: 0.6 parts of active silica ≤50um, 1.3 parts of alumina powder ≤50um, put into a three-dimensional mixer, add 1.2% PVA aqueous solution, mix for 0.8 hours, mix evenly, and get an interface liquid with a water content of 3%. The material is set aside, wherein the active silica powder and alumina powder are both powders that have been spray granulated;

[0092] Inner layer material: put 4 parts of silicon carbide 0.6-2mm, 4 parts of silicon carbide 0.125-0.25mm, 1.5 parts of silicon carbide ≤50um, and 1.5 parts of kaolin 0.045-0.075mm into a mixer, dry mix for 0.8 hours, add 1.2% PVA aqueous solution, and mix for another 0.8 hours. Mix evenly, the moisture content of the inner layer material is 4%, and the material is set aside for use;

[0093] 2. Pressing and drying of molding:

[0094] Take 1 / 2 outer layer material, 1 / 4 interface layer material, 1 / 2 bonding layer material, 1 / 4 interface material, inner layer material, 1 / 4 interface material, 1 / 2 bonding layer material, 1 / 4 interface material, 1 / 2 outer layer material, and place them in sequence into the mold cavity. After scraping and leveling the material, apply 100MPa pressure through a molding hydraulic press for high pressure molding to obtain a molded blank;

[0095] In terms of weight, the outer layer of plate-like corundum is 7 parts, the bonding layer is 8 parts, the inner layer of silicon carbide is 65 parts, the bonding layer is 8 parts and the outer layer of plate-like corundum is 7 parts; the mass ratio of the interface material layer, the main material layer and the interface material layer is 1.5:8.5:1.5.

[0096] The formed blanks are naturally stored for 36 hours, and after releasing the internal stress, they are placed in a drying room for drying. After drying at a temperature of 60-100°C, dry blanks with a moisture content of less than 1.5% are obtained, which are ready for loading into the kiln;

[0097] 3. High temperature firing:

[0098] The dried qualified blanks are sintered through the following procedures to obtain large-sized composite setter plates.

[0099]

[0100] Example 3

[0101] The method for preparing the large-size composite setter plate of the present invention comprises the following steps:

[0102] 1. Preparation of raw materials:

[0103] Outer layer material: put 6.0 parts of plate-shaped corundum powder ≤50um, 4.0 parts of plate-shaped corundum 0.075~0.18mm, and 1.0 parts of alumina powder ≤50um into a three-dimensional mixer, dry mix for 0.5~1 hour, add 1.5% PVA aqueous solution, mix for another hour, mix evenly, the moisture content of the outer layer liquid is 6%, and the material is set aside, wherein the plate-shaped corundum powder and alumina powder are powders treated by spray granulation;

[0104] Main material: 9.0 parts of zircon 0.075-0.15mm, put into a three-dimensional mixer, add 1.5% PVA aqueous solution, mix for 1 hour, mix evenly, the water content of the main material liquid is 6%, and the material is set aside;

[0105] Interface layer material: 1.0 part of active silica ≤50um, 2.0 parts of alumina powder ≤50um, put into a three-dimensional mixer, add 1.5% PVA aqueous solution, mix for 1 hour, mix evenly, the moisture content of the interface layer liquid is 5%, and the material is set aside. Among them, the active silica powder and alumina powder are powders that have been spray granulated;

[0106] Inner layer material: put 5.0 parts of silicon carbide 0.6-2mm, 4.5 parts of silicon carbide 0.125-0.25mm, 2.0 parts of silicon carbide ≤50um, and 2.0 parts of kaolin 0.045-0.075mm into a mixer, dry mix for 1 hour, add 1.5% PVA aqueous solution, and mix for another hour. Mix evenly, the water content of the inner layer liquid is 8%, and the material is set aside;

[0107] 2. Pressing and drying of molding:

[0108] Take 1 / 2 outer layer material, 1 / 4 interface layer material, 1 / 2 bonding layer material, 1 / 4 interface material, inner layer material, 1 / 4 interface material, 1 / 2 bonding layer material, 1 / 4 interface material, 1 / 2 outer layer material, and place them in sequence into the mold cavity. After scraping and leveling the material, use a molding hydraulic press to apply a pressure of 200MPa for high pressure molding to obtain a molded blank;

[0109] In terms of weight, there are 10 parts of plate-like corundum outer layer, 10 parts of bonding layer, 70 parts of silicon carbide inner layer, 10 parts of bonding layer and 10 parts of plate-like corundum outer layer; the mass ratio of interface material layer, main material layer and interface material layer is 1:9:2.

[0110] The formed blanks are naturally stored for 48 hours, and after the internal stress is released, they are placed in a drying room for drying. After drying at 100°C, dry blanks with a moisture content of less than 1.5% are obtained and are ready for loading into the kiln.

[0111] 3. High temperature firing:

[0112] The dried qualified blanks are sintered through the following procedures to obtain large-sized composite setter plates.

[0113]

[0114]

[0115] Comparative Example 1

[0116] The raw material of the main material layer is replaced with monoclinic zirconium dioxide particles, and the other components and preparation method are the same as in Example 1.

[0117] Comparative Example 2

[0118] The raw materials of the interface layer are replaced by silica particles and alumina particles, wherein the silica particles are 0.063-0.18 mm and the alumina powder is 0.075-0.18 mm. Other ingredients and preparation methods are the same as those in Example 1.

[0119] Comparative Example 3

[0120] The silicon carbide ≤50 um in the inner layer material is completely replaced with silicon carbide 0.6-2 mm. The other components and preparation method are the same as those in Example 1.

[0121] Comparative Example 4

[0122] In the outer layer material, all the corundum powder ≤50 um was replaced by plate-shaped corundum 0.075-0.18 mm. Other ingredients and preparation methods were the same as those in Example 1.

[0123] The setters obtained in Examples 1-3 and Comparative Examples 1-4 were taken to test their thermal shock resistance and the number of times of use.

[0124] Thermal shock resistance test method: YB / T376.1-1995 Thermal shock resistance test method for refractory products (water quenching method). The number of uses is counted according to the counting method, and the number of times the setter completes one operation is counted once, and the actual number of times the setter can be used is recorded.

[0125] The results are shown in Table 1.

[0126] Table 1 Setter performance test results

[0127] Thermal shock times (times) Use times (times) Example 1 62 83 Example 2 61 84 Example 3 65 86 Comparative Example 1 53 52 Comparative Example 2 62 56 Comparative Example 3 58 53 Comparative Example 4 45 56

[0128] It can be seen from Table 1 that the thermal shock times of the setter plate obtained by the present invention exceeds 60 times, and the number of uses can reach more than 80 times.

[0129] Zircon partially dissociates into a silicon dioxide liquid phase and a monoclinic zirconium dioxide phase under high temperature conditions, and reacts with a mixture of interfacially active silicon dioxide and alumina powder to form a complex network interlaced structure of zirconium corundum mullite doped with a badly zirconium crystal phase for toughening. When used as the main material of the bonding layer, the more monoclinic zirconium dioxide particles in Comparative Example 1 will aggregate, and the structure presented will destroy the network structure of the corundum mullite, affecting the strength of the bonding layer.

[0130] In Comparative Example 2, the raw materials of the interface layer replace the silica particles and alumina particles, which is not conducive to forming a corundum-mullite complex phase structure with the plate-like corundum micropowder of the outer layer. The single phase structure of the corundum phase or mullite phase may be formed, which affects the bonding strength of the support plate. At the same time, the outer layer may form a reticulation or peel off.

[0131] In Comparative Example 3, the amount of silicon carbide powder is reduced, which affects the reaction between the active silica powder and alumina powder of the bonding layer interface material and the silica powder, thereby affecting the formation of the zirconium corundum mullite complex network staggered structure bonding layer and reducing the bonding strength of the product.

[0132] In Comparative Example 4, reducing the amount of plate-like corundum powder affects the formation of the corundum-mullite structure of the outer layer, thereby affecting the strength and wear resistance of the surface layer, and the surface layer is prone to powdering and even peeling.

[0133] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A large-size composite setter, characterized in that: The support plate is formed by firing a stacked body, and the stacked body comprises, from top to bottom, in parts by weight: 5 to 10 parts of a plate-shaped corundum outer layer, 6 to 10 parts of a bonding layer, 60 to 70 parts of a silicon carbide inner layer, 6 to 10 parts of a bonding layer, and 5 to 10 parts of a plate-shaped corundum outer layer, wherein: The bonding layer includes an interface material layer, a main material layer, and an interface material layer from top to bottom, and the mass ratio of the interface material layer, the main material layer, and the interface material layer is 1-2:8-9:1-2; In parts by weight, the raw materials for preparing the interface material layer include: Active silicon dioxide ≤50um 0.5~1.0 parts, Alumina powder ≤50um 1-2 parts, In terms of weight, the raw materials for preparing the main material layer include: Zircon 0.075~0.15mm 8~9 parts.

2. The large-size composite setter according to claim 1, characterized in that: According to weight percentage, the raw materials for preparing the outer layer of tabular corundum include: Plate-shaped corundum powder ≤50um 5.0~6.0 parts, Plate-shaped corundum 0.075~0.18mm 3.0~4.0 parts, Alumina powder ≤50um 0.5~1.0 part.

3. The large-size composite setter according to claim 1, characterized in that: According to weight percentage, the raw materials for preparing the silicon carbide inner layer include: Silicon carbide 0.6~2mm 3.5~5.0 parts, Silicon carbide 0.125~0.25mm 3.0~4.5 parts, Silicon carbide ≤50um 1.0~2.0 parts, Kaolin 0.045~0.075mm 1.0~2.0 parts.

4. The method for preparing the large-size composite setter plate according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) Stacking molding: placing the raw materials into a mold in sequence to obtain a stacked body, wherein the stacked body comprises, from top to bottom, a plate-shaped corundum outer layer, a bonding layer, a silicon carbide inner layer, a bonding layer, and a plate-shaped corundum outer layer; after high-pressure molding, a molded blank is obtained; The bonding layer includes the interface material layer, the main material layer and the interface material layer from top to bottom. In parts by weight, the raw materials for preparing the interface material layer include: Active silicon dioxide ≤50um 0.5~1.0 parts, Alumina powder ≤50um 1-2 parts, In terms of weight, the raw materials for preparing the main material layer include: Zircon 0.075~0.15mm 8~9 parts, (2) drying the formed blank until the moisture content is less than 1.5% to obtain a dry blank; (3) Sintering the dry blank at 1400-1550°C and keeping it warm for 3-5 hours to obtain a combined fired plate.

5. The preparation method according to claim 4, characterized in that: The preparation method of the raw material of the main material layer is: take 8.0-9.0 parts of zircon with a size of 0.075-0.15 mm, add PVA aqueous solution, mix evenly, and obtain the main material liquid with a water content of 3-6%.

6. The preparation method according to claim 4, characterized in that: The preparation method of the raw materials of the interface material layer is as follows: take 0.5-1.0 parts of active silicon dioxide ≤50um and 1.0-2.0 parts of alumina powder ≤50um, add PVA aqueous solution, mix evenly, and obtain an interface material liquid with a water content of 2-5%.

7. The preparation method according to claim 4, characterized in that: Preparation method of raw materials for the outer layer of plate-like corundum: take 5.0-6.0 parts of plate-like corundum powder ≤50um, 3.0-4.0 parts of plate-like corundum 0.075-0.18mm, and 0.5-1.0 parts of alumina powder ≤50um, add PVA aqueous solution, mix evenly, and obtain outer layer liquid, whose water content is 3-6%.

8. The preparation method according to claim 4, characterized in that: The preparation method of the raw materials for the silicon carbide inner layer is as follows: 3.5-5.0 parts of silicon carbide 0.6-2mm, 3.0-4.5 parts of silicon carbide 0.125-0.25mm, 1.0-2.0 parts of silicon carbide ≤50um, and 1.0-2.0 parts of kaolin 0.045-0.075mm, add PVA and mix evenly to obtain an inner layer liquid with a water content of 3-8%.

9. The preparation method according to claim 4, characterized in that: The thickness of the main material layer is 1 to 1.5 mm, and the thickness of the interface material layer is 0.1 to 0.5 mm.

Citation Information

Patent Citations

  • Large-size composite load bearing plate with breathable bearing surface

    CN220624908U

  • Thermal insulation structure in polycrystalline silicon growing process

    CN103122480A

  • High-wear-proof high-thermal-shock-resistant fire-proof material and prefabricated furnace mouth part made from same

    CN103435361A

  • Wearing-resistant ceramic sintering loading plate and preparation method thereof

    CN106220203A

  • Bending-resistant high-temperature composite load bearing board and preparation method thereof

    CN111056825A